ผลของการปรึกษาเชิงจิตวิทยารายบุคคลตามแนวการบำบัดที่เน้นการยอมรับและความมุ่งมั่นแบบสั้นต่อความวิตกกังวลของผู้สูงอายุที่มีความเจ็บป่วยเรื้อรัง - สืบพงศ์ ฉัตรธัมมลักษณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This study was to examine the effect of individual counseling based on brief acceptance and commitment therapy on geriatric anxiety of older adults with chronic illness. A quasi-experiment with pretest-posttest control group design was employed. Participants, 42 older adults lived in Bang La Mung Elderly Center, were selected purposively according to inclusion criteria. Older adults were randomly assigned into the experimental and the control group (21 persons per group). Participants in the experiment group attended a weekly individual counseling sessions of 60-minute five sessions while participants in the control group recieved no treatment. Measure of geriatric anxiety was administrated to participants at before and after treatment. Data obtained were analyzed using an paired sample t-test and independent sample t-test. Findings were as follows: 1) When compared with their scores prior to group participation, participants in the experimental condition obtained significantly lower score on geriatric anxiety (p < .001). 2) When compared with their scores between experiment and control group, participants in the experimental condition obtained significantly higher score than control group on geriatric anxiety (p < .001).